Continuous glucose monitoring reveals a novel association between duration and severity of hypoglycemia, and small nerve fiber injury in patients with diabetes. Issue 12 (14th November 2022) - Gad, Hoda; Elgassim, Einas; Mohammed, Ibrahim; Alhaddad, Ahmad Yaser; Ahmed Hussein Zaky Aly, Hussein; Cabibihan, John-John; Al-Ali, Abdulaziz; Sadasivuni, Kishor Kumar; Haji, Aliyaa; Lamine, Neila; Khan, Adnan; Petropoulos, Ioannis N; et al.
Abstract : Objective: Continuous glucose monitoring (CGM) has revealed that glycemic variability and low time in range are associated with albuminuria and retinopathy. We have investigated the relationship between glucose metrics derived from CGM and a highly sensitive measure of neuropathy using corneal confocal microscopy in participants with type 1 and type 2 diabetes. Methods: A total of 40 participants with diabetes and 28 healthy controls underwent quantification of corneal nerve fiber density (CNFD), corneal nerve branch density (CNBD), corneal nerve fiber length (CNFL) and inferior whorl length (IWL) and those with diabetes underwent CGM for four consecutive days. Results: CNBD was significantly lower in patients with high glycemic variability (GV) compared to low GV (median (range) (25.0 (19.0–37.5) vs 38.6 (29.2–46.9); P = 0.007); in patients who spent >4% compared to <4% time in level 1 hypoglycemia (54-69 mg/dL) (25.0 (22.9–37.5) vs 37.5 (29.2–46.9); P = 0.045) and in patients who spent >1% compared to <1% time in level 2 hypoglycemia (<54 mg/dL) (25.0 (19.8–41.7) vs 35.4 (28.1–44.8); P = 0.04). Duration in level 1 hypoglycemia correlated with CNBD ( r = –0.342, P = 0.031). Duration in level 1 (181–250 mg/dL) and level 2 (>250 mg/dL) hyperglycemia did not correlate with CNFD ( P > 0.05), CNBD ( P > 0.05), CNFL ( P > 0.05) or IWL ( P > 0.05). Conclusions: Greater GV and duration in hypoglycemia, rather than hyperglycemia, are associated with nerve fiber loss in diabetes.